Kepimpinan pengajaran pengetua dan hubungannya dengan komitmen dan kepuasan kerja guru di sekolah berkesan di Negeri Perlis - Che Siah, Saad (2009)
The objective of this research is to observe the practice of instructional leadership by principals in two effective schools in Perlis. Vision, observation, appearance/'visibility', incentive, and support as independent variables. Whereas commitment and work satisfaction as dependent variables. The researcher also noticed the correlation between the instructional leadership of the principals with commitment and work satisfaction of the teachers. Samples of 83 teachers from two effective schools in Perlis were analyzed by Min and Pearson Correlation. Collection of data was done using questionnaires. The instrument by Mohd Nor Jaafar (2005), "Principal Instructional Management Rating Scale" that was designed by Hallinger and Murphy (1985), correlation "Pola Komitmen Kerja Guru Pelatih dengan Pola Pengajaran Dalam Praktikum" Collavelli and Bishop (1990) and satisfaction measuring instrument of teachers by Mohd Nor Jaafar (2005) were used to determine the relationship between instructional leadership of the principals with commitment and work satisfaction of the teachers. The min score of 3.4 for instructional leadership by principals is high with indicate that the principals have implemented such practice in their schools. The results also show that there is a significant relationship between instructional leadership of the principal with commitment (r = .44, p < .05) and work satisfaction of the teachers (r = .39, p < .05). Thus the null hypothesis is rejected and the alternative hypothesis is accepted